Impact of Clinical Genetics Attendance at a Gynecologic Oncology Tumor Board on Referrals for Genetic Counseling and BRCA Mutation Testing. Issue 5 (June 2016) - Cohen, Paul A.; Nichols, Cassandra B.; Schofield, Lyn; Van Der Werf, Steven; Pachter, Nicholas
Abstract : Objectives: The objectives of this work were to determine the proportion of eligible patients with ovarian cancer discussed at a gynecologic oncology tumor board who were referred for counseling and BRCA mutation testing; to compare referral rates before genetics attendance at the tumor board to referral rates after genetics attendance; and to ascertain the proportions of women with germline BRCA mutations. Materials and Methods: Eligible cases were identified from the minutes of the weekly Western Australian gynecologic oncology tumor board from July 1, 2013 to June 30, 2015. Patients with ovarian cancer who met eligibility criteria for genetics referral were identified and checked against the records of the genetic services database to ascertain whether a referral was received. Outcomes including attendance for counseling and results of mutation testing were analyzed. Results: Two hundred sixty-one patients were eligible for referral during the 24-month study period. One hundred six patients (40.6%) were referred for counseling and germline mutation testing. Of the eligible patients, 26.7% were referred in the 12 months before genetics attendance at the tumor board compared to 51.7% of the eligible patients in the 12 months after genetics attendance ( P ⩽ 0.0001). Ninety-seven patients were offered BRCA mutation testing, and 73 underwent testing with 65 results reported to date. Twenty-two patients (33.8 %) tested positive for a germline BRCA mutation. Conclusions: Patients with ovarian cancer had a high rate of BRCA mutations. Attendance of a genetics service at a tumor board was associated with an improved rate of referral of patients for genetic counseling and BRCA mutation testing.